Social Commandments in the Pre-Islamic Era: A Literary Study - Abbas, Noora obaid (Journal of Humanities & Social Sciences, 2021)
The study aimed at demonstrate the values ​​and ideals in the heritage of pre-Islamic literature, as a model the commandments that carry the wisdom of sincere experiences, in terms of implanting human values ​​through the branches of the Arabic language, especially prose and poetry, and extracting the lofty values ​​objectives from these commandments that support the linguistic, human and spiritual skills of society.The study used the analytical descriptive method. The study revealed that will literature in the pre-Islamic era is an independent art that deals with special issues that distinguish it from all other literary arts, because it charts an independent path for itself, which was manifested in the utilization of personal experience resources, acquired knowledge and high moral values.The study also recommended that to make use of the pre-Islamic commandments in order to become an educational method, because it contains a high direction for what society should be.
Keywords: Al-Jahili; commandments; social; poets; spiritual values